A LITERATURE REVIEW OF DIGITAL MARKETING STRATEGIES TO BUILD BRAND AWARENESS FOR CHILDREN'S EDUCATIONAL FLASHCARDS BUSINESS THROUGH INSTAGRAM: A CASE STUDY OF FLASHY - Sharfina Andzani Minhalina; Kharisma Nur Devyanti; Wien Kuntari (This journal is published by the Vocational School of Universitas Sebelas Maret., 2025)
Flashy is a business that sells educational flashcards for children and utilizes Instagram as the primary platform to reach its target audience and enhance brand awareness. This research aims to analyze Flashy’s digital marketing strategies in building brand awareness through Instagram. The study employs a qualitative approach by conducting content analysis on Flashy's Instagram account (@by.flashy), focusing on the types of content posted, posting frequency, utilization of Instagram features, and audience interaction. The results indicate that promotional content is the most effective in attracting audience attention, while educational content plays a vital role in fostering brand loyalty. Consistent posting frequency is essential in maintaining engagement, and the use of Instagram’s Reels feature has proven to be highly effective in reaching a broader audience. Furthermore, interaction through Direct Messages (DM) helps build stronger connections with the audience, although response speed needs improvement, especially during busy periods. Overall, Flashy’s marketing strategy on Instagram is relatively successful in increasing brand awareness, but there is still room for improvement in terms of consistency and responsiveness. This study provides practical recommendations for small businesses to optimize their digital marketing strategies on social media platforms like Instagram.